Pengaruh Audit Tenure, Ukuran Perusahaan dan Spesialisasi Industri terhadap Kualitas Laporan Keuangan - Ita Andriyani; Iman Waskito (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2026)
This study aims to investigate the impact of audit tenure, company size, and auditor industry specialization on the quality of financial reports in non-cyclical consumer goods companies listed on the Indonesia Stock Exchange from 2020 to 2024. Financial report quality is proxied using a non-modified audit opinion and measured using the dummy. The sampling technique used was purposive sampling, which resulted in 425 research samples from 660 observations. Data were analyzed using logistic regression analysis using IBM SPSS 23. The results showed that company size had a significant effect on the quality of financial reports, while audit tenure and auditor industry specialization had no effect on the quality of financial reports. Keywords: Financial Report Quality; Audit Tenure; Company Size; Auditor Industry Specialization; Unmodified Audit Opinion